2011
DOI: 10.3382/ps.2010-00961
|View full text |Cite
|
Sign up to set email alerts
|

Feather pecking behavior in laying hens: Hypothalamic gene expression in birds performing and receiving pecks

Abstract: Feather pecking (FP) is a welfare and economic problem in the egg production sector. Beak trimming, the current method used to reduce FP, is also criticized. The present study used gene expression to explore the biological mechanisms underlying this behavior, which could lead to a greater understanding of the cause and a tool to mitigate the problem. White Leghorn hens performing and receiving FP, as well as neutral control birds, were identified on a commercial farm. Hypothalamic RNA from 11 peckers, 10 victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 51 publications
0
45
0
2
Order By: Relevance
“…Chickens from an HFP line were found to have significantly higher locomotor activity compared with chickens from an LFP (Kjaer, 2009;Lutz et al, 2016). Other behaviors, such as those involved in aggression (Bessei et al, 2013;Bennewitz et al, 2014), exploration (de Haas et al, 2010Brunberg et al, 2011) and fear Boegelein et al, 2014, Grams et al, 2015b have been reported to be associated with feather pecking and may have a complementary effect on this behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Chickens from an HFP line were found to have significantly higher locomotor activity compared with chickens from an LFP (Kjaer, 2009;Lutz et al, 2016). Other behaviors, such as those involved in aggression (Bessei et al, 2013;Bennewitz et al, 2014), exploration (de Haas et al, 2010Brunberg et al, 2011) and fear Boegelein et al, 2014, Grams et al, 2015b have been reported to be associated with feather pecking and may have a complementary effect on this behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Fearfulness in chickens is influenced by multiple factors such as previous experience, housing conditions, interaction with humans, and genetic differences (Jones and Faure, 1981;Rodenburg et al, 2013). Individual variation is an important factor to consider in behavioural studies (Brunberg et al, 2011;Rodenburg et al, 2013;Bessei and Kjaer, 2015), and fearfulness is thought to vary on an individual bird level due to differences in brain morphology and serotonin turnover (Gruss and Braun, 1997;Rodenburg et al, 2013). While it is generally believed that there is a negative correlation between range use and fearfulness, very few studies have investigated this association, and the relationship between range use, fearfulness and SFP is relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Feather pecking and cannibalism are concerning welfare problems in poultry farming, and a major topic of welfare research in laying hens [1-4]. Severe feather pecking compromises the victim’s welfare through physical pain and chronic fear, but also signals that the welfare of the perpetrator is being compromised, leading to the development of this maladaptive coping mechanism [5].…”
Section: Introductionmentioning
confidence: 99%